Design and Implementation of Network Simulator for High-Level Naval Ship System - Min-Hui Jang; Hyeong-Jin Kim; Young-Keun Go; Nak-Jung Choi; Jae-Ho Lee; Jae-Hak Yu; Jae-Min Lee; Tae-Soo Jun; Dong-Seong Kim (IEEE Access)
Operational naval ship systems rely on advanced sensors and equipment to detect targets and manage weapon control and engagement. However, their growing complexity, driven by technological advancements and the increasing integration of clients and servers, necessitates changes in system architecture and network structure. To address these challenges, this paper presents the design and implementation of NSNS (Network Performance Evaluation Simulator for Naval Ship Combat System), a specialized simulator for advancing research on naval ship system networks. The NSNS provides a robust environment for performance analysis by leveraging the unique characteristics of naval ship combat system nodes and network properties. Its reliability was validated through comparisons with real-world system measurements, demonstrating consistent trends and acceptable error rates. This research underscores the importance of dedicated simulation tools for validating new naval network architectures and enhancing network reliability and availability in wartime scenarios.